Teaching cybersecurity : a handbook for teaching the cybersecurity body of knowledge in a conventional classroom - Shoemaker, Dan; Sigler, Kenneth; Shoemaker, Tamara, (Cyber security expert) (Boca Raton, FL : CRC Press, 2023)
"Let's be realistic here. Ordinary K-12 educators don't know what "cybersecurity" is and could probably care less about incorporating it into their lesson plans. Yet, teaching cybersecurity is a critical national priority. So, this book aims to cut through the usual roadblocks of confusing technical jargon and industry stovepipes and give you, the classroom teacher, a unified understanding of what must be taught. That advice is based on a single authoritative definition of the field. In 2017, the three societies that write the standards for computing, software engineering, and information systems came together to define a single model of the field of cybersecurity. It is based on eight building blocks. That definition is presented here. However, we also understand that secondary school teachers are not experts in arcane subjects like software, component, human, or societal security. Therefore, this book explains cybersecurity through a simple story rather than diving into execution details. Tom, a high school teacher, and Lucy, a middle school teacher, are tasked by their district to develop a cybersecurity course for students in their respective schools. They are aided in this by "The Doc," an odd fellow but an expert in the field. Together they work their way through the content of each topic area, helping each other to understand what the student at each level in the educational process has to learn. The explanations are simple, easy to understand, and geared toward the teaching aspect rather than the actual performance of cybersecurity work. Each chapter is a self-contained explanation of the cybersecurity content in that area geared to teaching both middle and high school audiences. The eight component areas are standalone in that they can be taught separately. But the real value lies in the comprehensive but easy-to-understand picture that the reader will get of a complicated field"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer networks -- Security measires -- Study and teaching; Internet -- Security measures -- Study and teaching; EDUCATION / Teaching Methods & Materials / Science & Technology; COMPUTERS / Security / General; COMPUTERS / Cryptography